Study of Deformation of Tungsten and Its Alloys for Applications in Fusion Reactors - Carabajal, Catalina; Gervasoni, Juana Luisa; Fernández, Ariel (David Publishig, 2020)
Fil: Carabajal, Catalina. Comisión Nacional de Energía Atómica; Argentina